Karakter Fisik dan Kimia Sumber Air Canal di Lahan Rawa Pasang Surut untuk Budidaya Perikanan - Marsi, Marsi; Susanto, Rubiyanto H; Fitrani, Mirna (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
Tidal lowland is a potential land for aquaculture, however it should be manage intensively in order to give a good and sustainable contribution for society. Tidal fenomenon and rainfall will interacted with water quantity and quality which will used as fish media culture. Fish need optimal water to support its growth and survival. Based on measure and water analysis in two locations, at Mulyasari village, Tanjung Lago District, Banyuasin Regency, South Sumatera, tidal and rainfall gave effect to physical, chemical and biological of water quality and quantity. Related to the change of weather where in the second year (2016) the dry season was longer than rainy season since 2015,the rainfall was only about 200 mm- 310 mm/month. The lower of rainfall effected to the water level in canals and influent the brightness and turbidity, sea intrution that brought salinity about 5-15 ppt in the water.Acidity was also decline about 3.5-5 with ammonia- free reached 0.25 mg/L. Nitrate and nitrite were in common such a natural water condition, yet pyrite oxidized that caused the water and land tobe reddish yellow and looked like greasy in the surface. These condition would be harmfull for fish. The tidal and rainfall was also effect plankton abundance. The data shows that fitoplankton and zooplankton were higher in the canals than in the pond.